Combination of Alginate and Ginger Oil as Edible Coating Formulation for Reducing Pathogenic Bacteria in Litopenaeus vannamei - Amal, Ikhlasul; Yudiati, Ervia; Sedjati, Sri; Ighwerb, Mostafa Imhmed (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2023)
Litopenaeus vannamei is a world trade commodity that has a high economic value but is easily degraded. To maintain the quality, post-harvest peeled shrimp needs to be coated. The research objective was to determine the effectiveness of adding edible coatings with a formulation of alginate and ginger oil combination as a natural preservative for shrimp. The research method used was laboratory experimental with a completely randomized design (CRD). The treatments were additional peeled shrimp with different concentrations of alginate, i.e. 0 g, 1.5 g, and 3.0 g with two repetitions. The addition of 100 ml aquadest, 4 g CaCl2, 15 mL glycerol, and 1.5 mL of ginger oil was administered in every treatment. Total Plate Counts (TPC), Escherichia coli, and Vibrio cholerae were determined in initial condition, 3rd, and 6th days after the storage time in a 40C refrigerator.  The edible film test with 5 repetitions, including thickness, tensile strength, and break elongation. The results on TPC (5.00 x 105 CFU.g-1) and TPC of V. cholerae (Negative.25 g-1) show that all the treated shrimp meet the standard value (SNI 3457:2021) requirements. Most Probably Number of E. coli in alginate addition of 0 and 1.5 g i.e. <3 MPN.g-1 treatments, do not meet the requirements. The bacterial test and edible film mechanical properties showed that the addition of 3.0 g alginate was the most effective treatment compared to other treatments (α=0.05). A formulation of alginate and ginger oil combination is an effective edible coating for reducing the pathogenic bacteria of peeled shrimp L. vannamei.